2010
DOI: 10.2174/1874325001004020062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of 40 Consecutive Basal Thumb Prostheses and No CRPS Type I After Vitamin C Prophylaxis~!2009-10-04~!2009-12-30~!2010-02-17~!

Abstract: Complex regional pain syndrome (CRPS) type I may occur as complication after any type of surgery for basal joint arthritis of the thumb. We investigated prospectively in an ongoing study our results after a fully standardized treatment with a total joint prosthesis under vitamin C prophylaxis.Patients with trapeziometacarpal arthritis stage II or III according to Dell, and no benefit from conservative treatment, were selected to undergo joint replacement with a semi-constrained hydroxyapatite coated prosthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Calcitonin + 3 g/day vitamin C (N = 11) for 2 weeks ii. Pain relief in 73%, marked ↓ pain in 45% Uncontrolled prospective Arthritic joint replacement surgery [ 54 ] a 500 mg/day oral vitamin C (N = 34) for 50 days 0% CRPS cases Paget’s disease of bone [ 58 ] 3 g/day oral vitamin C (N = 16) for 2 weeks ↓ Pain in 50%, no pain in 20% (within 5-7 days) Case report Rheumatoid arthritis [ 56 ] 50 g IV vitamin C twice/week for 4 weeks Before: 100% pain (QLQ) After: 0% pain IV intravenous, VAS visual analog scale, QLQ quality of life questionnaire * P < 0.05 a Study was included in CRPS meta-analysis [ 48 52 ] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcitonin + 3 g/day vitamin C (N = 11) for 2 weeks ii. Pain relief in 73%, marked ↓ pain in 45% Uncontrolled prospective Arthritic joint replacement surgery [ 54 ] a 500 mg/day oral vitamin C (N = 34) for 50 days 0% CRPS cases Paget’s disease of bone [ 58 ] 3 g/day oral vitamin C (N = 16) for 2 weeks ↓ Pain in 50%, no pain in 20% (within 5-7 days) Case report Rheumatoid arthritis [ 56 ] 50 g IV vitamin C twice/week for 4 weeks Before: 100% pain (QLQ) After: 0% pain IV intravenous, VAS visual analog scale, QLQ quality of life questionnaire * P < 0.05 a Study was included in CRPS meta-analysis [ 48 52 ] …”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing joint replacement surgery for osteoarthritis were administered 0.5 g/day prophylactic vitamin C for 50 days post-surgery (Table 1 ) [ 53 , 54 ]. Although osteoarthritis of the carpometacarpo joint can be complicated by CRPS, no cases of CRPS were observed under vitamin C prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Es wurde in den Standarddatenbanken (PubMed, ScienceDirect, Cochrane Library) von 1997 bis März 2023 nach den Schlüsselwörtern CMC1, Daumengrundgelenk, Rhizarthrose, Totalgelenkimplantat, Prothese, Arthroplasty, Implantate gesucht, und zwar sowohl in englischer als auch in französischer Sprache, da viele Studien in französischer Sprache veröffentlicht wurden. Insgesamt wurden 4 216 Fälle von Totalendoprothesen an der Daumenbasis in 82 Studien aus den letzten 25 Jahren veröffentlicht 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 ...…”
Section: Tausende Implantiert Nur Wenige Dokumentiert – Literaturüber...unclassified
“…Noteworthy, earlier animal studies have suggested that there is a close relationship between recovery from anesthesia and extracellular ascorbic acid levels ( 2 ). Vitamin C has showed pain relieving effects ( 3 ) namely in complex regional pain syndrome ( 4 ), post herpetic neuralgia ( 5 ), migraine headache ( 6 ) and myalgia associated with the administration of suxamethonium ( 7 ). Moreover, the placebo tablet should be identical-looking with similar color, taste, and smell with the treatment drug.…”
mentioning
confidence: 99%